Survival of bifidobacteria administered to calves - Vlková, E; Grmanová, M; Killer, J; Mrázek, J; Kopecný, J; Bunesová, V; Rada, V (Folia microbiologica, 2010)
Twenty-five bifidobacteria were isolated from feces of calves. Isolates were identified, and their functional properties and antimicrobial activity were determined. From 10 strains with suitable properties rifampicin-resistant mutants (RRBs) were prepared and mixture of RRBs was administered to 2-d-old calves. These strains were identified by sequencing as Bifidobacterium animalis ssp. animalis (6 strains), B. thermophilum (2 strains), B. choerinum (1 strain) and B. longum ssp. suis (1 strain). The control group was without probiotic treatment. Survival ability of administered bifidobacteria was monitored in fecal samples by cultivation on modified TPY agar supplemented with mupirocin, acetic acid, and rifampicin. Administered bifidobacteria survived in gastrointestinal tract of calves for at least 60 d. Other bacteria were also determined after cultivation using fluorescence in situ hybridization (FISH). Bifidobacteria and lactobacilli dominated in fecal microflora. Significantly lower amounts of E. coli and higher amounts of bifidobacteria and total anaerobes were found in the treated group relative to the control group.
Keywords: Cattle; hybridizace in situ; Feces; Cluster Analysis; Colony Count, Microbial; fylogeneze; mikrobiální viabilita; techniky typizace bakterií; probiotika; skot; Phylogeny; antibakteriální látky; Microbial Sensitivity Tests; Bacteria; shluková analýza; počet mikrobiálních kolonií; Gastrointestinal Tract; In Situ Hybridization; Time Factors; DNA, Bacterial; DNA bakterií; Animals; Microbial Viability; Anti-Bacterial Agents; zvířata; mikrobiální testy citlivosti; Bifidobacterium; časové faktory; gastrointestinální trakt; Probiotics; Bacterial Typing Techniques; feces